Trial and Error: Finding Your Calling Through Fearless Exploration - Jaiswal, Sarjana (My University, 2019)
This summer started out a little bumpy, as I struggled with an internship and organization that I was excited about but was not learning enough in. The chasm between my vision for the summer and the reality was growing wider when I stumbled upon an opportunity at the Indian Council for Research on International Economic Relations (ICRIER) in New Delhi. I went on to work with a team that was researching the existing scenario of solid waste management in India under a broader theme of ‘Challenges and Opportunities of Urbanization’. I performed quantitative and qualitative data analysis and drew comparisons between some major cities of India. I contributed to determining practical ways to upgrade the system and gained insight on various issues faced by a developing economy. My presentation will expand on how my two internships taught me to navigate tricky situations, take initiative, and explore without hesitation.
Imperfect Internships: It’s Not the End!